The Hyponatremia Epidemic: A Frontier Too Far? - Drake-Holland, Angela J.; Noble, Mark I. M. (Frontiers in Cardiovascular Medicine, 2016)
Hyponatremia is the most common electrolyte abnormality, and is often neglected, especially in elderly and seemingly terminal patients. Hyponatremia can be asymptomatic or can cause symptoms ranging from nausea and lethargy to convulsions and coma. This condition has become increasingly common over time with a similar time course to the increase in adoption of low salt diets. The popularisation of low salt may not be justified in people with normal kidney function in whom the compatible statistically based evidence that salt causes hypertension has been challenged by experimental evidence to the contrary.